Effect of macronutrient levels on Chlorella vulgaris cultivation for long duration spaceflights and space settlements. (May 2023) - Aguda, Remil; Stelly, Cody; Fonseca, Lucile; LeBoeuf, Shayla; Massiha, Shahrzad; Chistoserdov, Andrei; Holmes, William E.; Hernandez, Rafael; Zappi, Mark E.; Revellame, Emmanuel D.
Abstract: To expand space explorations into space settlements, there is a need for the establishment of a sustainable, closed-loop life support system. Systems involving microalgae are promising, as they could simultaneously revitalize air (i.e., CO2 to O2 conversion), reclaim water (i.e., nutrient biofixation/recycling), and provide food supplement (i.e., biomass). This would entail microalgal cultivation in human-derived wastes (both gas and liquid), which could provide challenges on system tolerance, particularly on the levels of nutrients in these wastes. In this work, the effect of macronutrient [Carbon (C), Nitrogen (N), and Phosphorus (P)] levels on the phototrophic growth of Chlorella vulgaris UTEX 2714 was investigated using synthetic wastewater. This was done to determine the range of macronutrient levels that are suitable for sustained microalgal growth. The highest biomass concentration was achieved when the microalga was axenically cultivated in 71 mg C/L, 64 mg N/L, and 13 mg P/L. With an equivalent C:N:P mass ratio of 5.5:5:1, this cultivation condition was significantly different from the ideal C:N:P of 41:7:1, suggesting a C-limited growth environment. This was also supported by 99.9% C consumption, while only consuming 56% and 72% of N and P, respectively. These results indicate that during space cultivation, incremental amount of C must be added to the microalgal system to improve the overall C:N:P of the process and to enhance N and P consumption, while ensuring that the C level is below the inhibitory threshold limit. Based on these results, together with human-derived wastes data from the International Space Station, a microalgal photobioreactor configuration was proposed. Highlights: Uninhibited growth of C. vulgaris in HCO3 −, NH4 +, and H2 PO4 − is carbon-limited. Incremental input of CO2 could improve the consumption of nitrogen and phosphorus. The threshold macronutrient levels could be used to estimate bioreactor sizes.